2016
DOI: 10.1097/meg.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-induced bowel dysfunction in healthy volunteers assessed with questionnaires and MRI

Abstract: Experimental OIBD in healthy volunteers was induced during oxycodone treatment. This model has potential for future interventional studies to discriminate the efficacies of different laxatives, peripheral morphine antagonists and opioid treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 42 publications
6
53
1
Order By: Relevance
“…This strengthens the speculation of water reabsorption counterbalancing a potential increase in stool volume, which may be why no increase in descending fecal volume could be found. Since opioid treatment has been shown to increase transit time in the rectosigmoid colon, and more firm stool assessed via the Bristol Stool Form Scale in the same study subjects, one might have expected an increase in stool dryness in the rectosigmoid colon. However, baseline‐corrected values from both the T 2 ‐weighted and LAVA‐Flex images indicated no change in stool dryness in the rectosigmoid colon.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This strengthens the speculation of water reabsorption counterbalancing a potential increase in stool volume, which may be why no increase in descending fecal volume could be found. Since opioid treatment has been shown to increase transit time in the rectosigmoid colon, and more firm stool assessed via the Bristol Stool Form Scale in the same study subjects, one might have expected an increase in stool dryness in the rectosigmoid colon. However, baseline‐corrected values from both the T 2 ‐weighted and LAVA‐Flex images indicated no change in stool dryness in the rectosigmoid colon.…”
Section: Discussionmentioning
confidence: 98%
“…All data analysis was performed using a semiautomatic volumetric segmentation platform (MatLab v. R2016a, MathWorks, Natick, MA) that has been used in several other studies . In short, the observer outlines a coarse region of interest encapsulating the colon on each of the 35–40 abdominal coronal images where the colon is shown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with short-term use, opioid analgesic therapy can result in symptoms of constipation. The use of opioids for 5 days produced nearly twofold patient-reported symptoms of constipation in opioid-treated patients vs placebo patients ( P <0.001) and an objectively measured 41% segmental colorectal volume increase in the cecum and/or ascending colon ( P =0.005 vs placebo) 2. After 5 days of oxycodone therapy, the median gastrointestinal (GI) transit time increased from 22.2 hours to 43.9 hours ( P <0.001) 3.…”
Section: Introductionmentioning
confidence: 98%
“…We have previously developed a model of OIC in healthy volunteers and shown that oxycodone causes symptoms of OIC, prolongs regional GI transit times, 11 and increases colorectal volumes. 12 The model for OIC in healthy volunteers allows for interventional studies of OIC not influenced by confounders such as comorbidity, activity level or concomitant drug that can all cause constipation and hence make studies in patients difficult to interpret. We hypothesized that combined prolonged-release (PR) oxycodone/naloxone tablets would be more effective than PR oxycodone plus conventional laxative treatment with macrogol 3350 in preventing oxycodone-induced OIC.…”
Section: Introductionmentioning
confidence: 99%